Habitat conservation prioritization: A floristic approach applied to a Mediterranean wetland network. (4th July 2017) - Angiolini, C.; Viciani, D.; Bonari, G.; Lastrucci, L.
Abstract: The importance of plant communities for conservation purposes is recognized in their inclusion in the "Habitat Directive" (92/43 EEC), that relates habitat types to plant community syntaxonomic units. However, habitat definitions in the Habitat Directive lead to several inaccuracies in local habitat characterization. Several wetland plant communities (and their corresponding habitats), rare in the Mediterranean basin, are not included in the Habitat Directive. This study proposes criteria for assessing the conservation importance of habitats. It deals with plant community types at the alliance level, as promising units for setting conservation priorities. The principle criteria considered as drivers for setting alliance conservation values are the distribution and abundance of plant species of conservation interest and their fidelity to a plant community. Multivariate methods were used, and a quantitative floristic index of alliance conservation priority was created. This procedure was applied to an important wetland in central Italy. Results emphasize: (i) high conservation values of some alliances not listed in the Habitat Directive, confirming various gaps in the current conservation law affecting Mediterranean wetlands; (ii) that habitats widely distributed in other biogeographical areas, may greatly underestimate their conservation importance in Mediterranean region; (iii) need to consider regional peculiarities when setting conservation priorities.